Application Study of Economic Residential Air Conditioning System - 李革; 曲晓萍 (Zhileng xuebao)
On the basis of the current energy and electricity's usage in our country, a new residential air conditioning system-the refrigeration potential energy storage system with economy and environmental protection is presented. The economic analysis, advantages and other properties of this system are described. This refrigeration system with potential energy storage has a very good development prospect.